Hallazgo de cisticantos (Acanthocephala: Polymorphidae) en el cangrejo terrestre Gecarcinus planatus Stimsom de Isla Socorro, Archipiélago Revillagigedo, México - Pérez Chi, Alicia; Sánchez Manzano, Rosa María; Ramírez San Juan, Eduardo; Sánchez Salazar, María Elena (Instituto de Ecología, A.C., 2001)
This is the first record of an acanthocephalan cystacanth (Acanthocephala: Polymorphidae) parasitizing the crab Gecarcinus planatus collected in the Socorro island, Revillagigedo Archipelago, Mexico. The highest prevalence was found at coastal localities (60% vs. 3.5%) and was significantly higher in males than in females (50% vs. 16%). Cystacanth numbers were positively correlated to the size of parasitized crabs (r=0.614; p<0.01). Since these crabs are included in the diet of the night heron, red-tailed hawk and feral cat, it is likely that one or more of these species are the definitive host for this acanthocephalan.